2020
DOI: 10.1002/cplu.202000112
|View full text |Cite
|
Sign up to set email alerts
|

Surface Nanostructures Based on Assemblies of Polymer Brushes

Abstract: Studies on the fabrication of hierarchical surface nanostructures have significantly promoted the development of materials with new surface properties and functionalities. In this Minireview, progress on the fabrication of surface nanostructures based on surface organization of polymer brushes are outlined. In the past decades, self-assemblies of polymer brushes, including homopolymer, block-copolymer and mixed-polymer brushes, have aroused great interest in the fields of chemistry and materials science. Recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 95 publications
0
18
0
Order By: Relevance
“…Figure c shows a plot of ln­([M] 0 /[M] t ) versus polymerization time. The plot was separated into three stages by two specific points at 5 and 10 h. In a dispersion polymerization, a turning point on a plot of ln­([M] 0 /[M] t ) versus polymerization time represents the onset of micellization of the generated BCP in the solution and a change from homogeneous to heterogeneous polymerization. , In this research, with chain extension of PS to a critical length, the PS homopolymer chains and PS brushes collapse on the silica particles, which results in the formation of PS domains and a change from homogeneous RAFT polymerization to heterogeneous surface polymerization. , TEM results (Figure ) indicate that no surface self-assemblies are observed at 5 h, but after that point, surface nanostructures are formed. So the turning point at 5 h represents the onset of surface self-assembly on silica particles.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure c shows a plot of ln­([M] 0 /[M] t ) versus polymerization time. The plot was separated into three stages by two specific points at 5 and 10 h. In a dispersion polymerization, a turning point on a plot of ln­([M] 0 /[M] t ) versus polymerization time represents the onset of micellization of the generated BCP in the solution and a change from homogeneous to heterogeneous polymerization. , In this research, with chain extension of PS to a critical length, the PS homopolymer chains and PS brushes collapse on the silica particles, which results in the formation of PS domains and a change from homogeneous RAFT polymerization to heterogeneous surface polymerization. , TEM results (Figure ) indicate that no surface self-assemblies are observed at 5 h, but after that point, surface nanostructures are formed. So the turning point at 5 h represents the onset of surface self-assembly on silica particles.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, polymerization-induced surface self-assembly (PISSA) approach was demonstrated to be a versatile procedure for the synthesis of hierarchical surface nanostructures on solid surfaces. In a typical PISSA process, surface anchored reversible addition–fragmentation chain transfer agent (RAFT CTA) and “free” macro-CTA are used as co-RAFT agents in RAFT-mediated dispersion polymerization. Driven by the minimization of surface energy, the generated “free” block copolymer (BCP) chains and the polymer brushes coassemble into surface nanostructures, and a variety of surface morphologies ranging from isolated spherical surface micelles to fused surface micelles and to layered structures are fabricated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymers prepared by RAFT have been used in many different fields, notably in preparation of biomaterials (implants, scaffolds, coatings, drug, gene delivery, etc. ), [ 226–230 ] sensing and detection, [ 231,232 ] coatings and patterning, [ 233–235 ] electronics, [236] nanocomposite, [ 235,237–240 ] and vitrimers. [ 241 ] One of the most recent and emerging applications of polymers and nanoparticles prepared by RAFT is membranes for separation.…”
Section: Novel Applications Of Raftmentioning
confidence: 99%
“…Spherical nanoparticles decorated by grafted macromolecules are promising for broad application in diverse high-tech fields, including drug-delivery systems in personal medicine and eco-friendly methods of oil production. They are the subject of a huge number of experimental, computer, and theoretical studies.…”
Section: Introductionmentioning
confidence: 99%